Uncovering the genomic basis of phenological traits in Chouardia litardierei (Asparagaceae) through a genome-wide association study (GWAS) - Šarančić, Sara Laura; Pleić, Nikolina; Križanović, Krešimir; Surina, Boštjan; Mitić, Damjan; Radosavljević, Ivan (Frontiers in Plant Science, 2025)
Chouardia litardierei (Asparagaceae) is a non-model, perennial species characterized by exceptional ecological plasticity. In this research, we studied the genetic architecture underlying several phenological traits in selected ecologically diverged populations of this species. We conducted a genome-wide association study (GWAS) to identify genomic regions linked to the following populations-specific phenological traits: Beginning of Sprouting (BOS), Beginning of Flowering (BOF), Flowering Period Duration (FPD), and Vegetation Period Duration (VPD). Combining phenological data from a common garden experiment with an SNP dataset obtained through the ddRAD-seq approach, we identified numerous loci associated with these traits using single- and multi-locus GWAS models. Narrow-sense heritability estimates were high for all traits, with the VPD trait showing the highest estimate (86.95%), emphasizing its importance for local adaptation. Functional annotation of associated genomic regions revealed key protein families involved in flowering time regulation, vegetative growth timing, and stress adaptation. These findings provide insights into the molecular mechanisms of local adaptation in C. litardierei’s populations from different habitats, emphasizing the role of genetic factors in phenological trait variation and ecological divergence across populations.